FIP200 is Involved in Murine Pseudomonas Infection by Regulating HMGB1 Intracellular Translocation - Yi Li; Chang-pei Gan; Shuang Zhang; Xi-kun Zhou; Xue-feng Li; Yu-quan Wei; Jin-liang Yang; Min Wu (Cellular Physiology and Biochemistry, 2014)
Background: FIP200, a critical autophagy initiating protein, can participate in numerous cellular functions including cancer development; however, its functional role in P. aeruginosa infection of alveolar macrophages is unknown. Methods: To investigate the role of FIP200 in host defense, we transfected murine alveolar macrophage MH-S cells with FIP200 siRNA. Having confirmed that FIP200 knockdown inhibited PAO1-induced autophagosme formation, we sought to characterize the underlying signaling pathways by immunoblotting. Further, we used fip200 KO mice to study the effects of fip200 deficiency on HMGB1 translocation. Results: We showed that Pseudomonas PAO1 strain infection facilitated autophagosome formation, whereas knockdown of FIP200 inhibited autophagosome formation and HMGB1 expression in MH-S cells. Silencing FIP200 impaired the translocation of HMGB1 to cytosol of MH-S cells and almost abolished acetylation of HMGB1 during PAO1 infection. In contrast, FIP200 overexpression facilitated the cytosol translocation of HMGB1 from nuclei and increased acetylation of HMGB1 in PAO1-infected MH-S cells. Importantly, expression and acetylation of HMGB1 were also significantly down-regulated in fip200 KO mice following PAO1 infection. Conclusions: Collectively, these findings elucidate that FIP200 may regulate expression and translocation of HMGB1 during PAO1 infection, which may indicate novel therapeutic targets to control pulmonary infection.